Internet addiction influences life satisfaction through social support among Chinese college students: a moderated mediation model of grit - Ma, Tingting; Li, Jianan; Lee, Chang Seek (Frontiers in Psychology, 2025)
The prevalence of Internet addiction among college students has gained significant attention in recent years. Research has established a negative relationship between Internet addiction and life satisfaction, although the underlying mechanisms are not fully understood. The present study aims to examine the relationship between Internet addiction, grit, social support, and life satisfaction. A random sampling method was used to recruit 304 Chinese college students to complete a questionnaire that included measures of Young’s Internet Addiction Scale, Multidimensional Scale of Perceived Social Support, Satisfaction with Life Scale, and 12-Item Grit Scale. For data analysis, SPSS, PROCESS macro and AMOS 23 were used to conduct confirmatory factor analysis, descriptive statistics analysis, reliability analysis, correlation analysis, and moderated mediation analysis. The results revealed that Internet addiction was negatively correlated with life satisfaction, and social support plays a mediating role between them. Moreover, grit moderated the mediation effect of social support in the relationship between Internet addiction and life satisfaction. This suggests that Internet addicts with higher levels of grit are less likely to experience a significant decline in social support. The study provides a deeper insight into the mechanisms through which Internet addiction hampers life satisfaction, suggesting that the influence may be channeled through social support. However, fostering a strong sense of grit could serve as a protective factor against the adverse impacts of internet addiction on life satisfaction. The broader implications for both research and practical applications in the field are subsequently elaborated.